Charles Darwin in Cambridge the most joyful years - Van Wyhe, John 1971- (World Scientific Pub. Co., 2014)
Charles Darwin's years as a student at the University of Cambridge were some of the most important and formative of his life. Thereafter he always felt a particular affection for Cambridge. For a time he even considered a Cambridge professorship as a career and sent three of his sons there to be educated. Unfortunately the remaining traces of what Darwin actually did and experienced in Cambridge have long remained undiscovered. Consequently his day-to-day life there has remained unknown and misunderstood. This book is based on new research, including newly discovered manuscripts and Darwin publications, and gathers together recollections of those who knew Darwin as a student. This book therefore reveals Darwin's time in Cambridge in unprecedented detail